PELAKSANAAN PENERBITAN SERTIFIKAT PENGGANTI HAK MILIK ATAS TANAH KARENA HILANG - Syarifuddin, Muhammad; Yanti, Febbi Rahma (Jurnal Ilmu Hukum Kanturuna Wolio, 2024)
This research aims to determine the implementation of the issuance of replacement certificates for land ownership rights due to loss (case study at the Baubau City Land Office). Article 1 number 1 Government Regulation no. 24 of 1997 concerning Land Registration states that Land Registration is a series of activities carried out by the Government continuously, continuously and regularly, including collecting, processing, bookkeeping, and presenting and maintaining physical data and juridical data, in the form of maps and lists, regarding the field of - plots of land and apartment units, including the provision of certificates of proof of title to plots of land to which there are already existing rights and ownership rights to apartment units as well as certain rights that encumber them. The method used in this research is descriptive analysiswhich means that from this research it is hoped that a detailed and systematic picture of the problems to be studied can be obtained. Analysis is meant to be based on descriptions, the facts obtained will be analyzed carefully to answer the problem. The results of this research show that the reissuance of lost replacement certificates at the Baubau City Land Agency is in accordance with the applicable standard operational procedures as stated in Government Regulation No. 24 of 1997 concerning Land Registration and Regulation of the Minister of State for Agrarian Affairs Number 3 of 1997 concerning Implementation Provisions Government Regulation Number 24 of 1997 concerning Land Registration, and the inhibiting factors faced by the Baubau City Land Agency in implementing the issuance of a replacement certificate for land ownership due to loss is the lack of a photocopy of the lost certificate and the lack of documents which are a requirement for the application for the issuance of a second replacement certificate